Reflecting on the Implementation of Online English Learning in Islamic Higher Education: Lecturers and Students’ Perspectives - Madehang, Madehang; Masruddin, Masruddin; Iksan, Muhammad (International Journal of Asian Education, 2024)
The penetration of technology into education has rebounded since the emergence of the COVID-19 pandemic era, especially in bridging the practice of online learning in schools and universities. Reflecting on the practice of online learning, teachers and students give various perceptions. Some benefits and obstacles are mentioned. This descriptive study focused on investigating the perception of lecturers and students toward online language learning in Islamic higher education. The data were collected from teachers and students in three Islamic Higher Education, namely the State Islamic Institute of Palopo, the State Islamic Institute of Bone, and the State Islamic University of Makassar. The questionnaire was used to collect data from 12 lecturers and 86 students participating. In contrast, the interview was used to gain more profound information about the lecturers’ experience and opinions about implementing online learning. From both the questionnaire and the interview, the writers concluded that Lecturers and students in Islamic higher education in South Sulawesi have a positive view of online EFL learning. They value the flexibility, access to resources, and networking opportunities it provides. Students appreciate the ability to manage their learning independently, connect with diverse learners, and engage with various language aspects. However, there's a need for improvements in technology familiarity, stable internet access, access to online learning equipment, and pedagogical training for lecturers to enhance the online learning experience further.